Econophysics: Background and Applications in Economics Finance, and Sociophysics - Constantin Manea (Amfiteatru Economic)
Ever since the official birth of the new transdisciplinaryfield of econophysics, whose admitteddate is the very beginning of the last decade of thetwentieth century, a number of Romanian researchershave authored some highly appreciated and frequentlycited papers published in international literature,especially articles. Such authors whom we couldmention, in a purely random selection, and inalphabetical order only, are Mircea Bulinski, RaduChişleag, Adrian Drăgulescu, Mircea Gligor,Margareta Ignat, Sorin Solomon, Ion Spânulescu, etc.